Intact corneal epithelium is essential for the prevention of stromal haze after laser assisted in situ keratomileusis. Issue 2 (1st February 2001) - Nakamura, Kunihiko; Kurosaka, Daijiro; Bissen-Miyajima, Hiroko; Tsubota, Kazuo
Abstract : AIMS: To determine the effect of intact corneal epithelium on stromal haze and myofibroblast cell formation after excimer laser surgery. METHODS: Denuded epithelium alone, photorefractive keratectomy (PRK), laser in situ keratomileusis (LASIK), or LASIK with denuded epithelium was performed in rabbit eyes. Postoperative anterior stromal haze was assessed employing a standard scale. Immunohistochemical methods were used to detect alpha smooth muscle actin (α-SMA), a marker for myofibroblastic cells, and type III collagen in subepithelial corneal tissue. RESULTS: Three weeks after surgery, the presence of α-SMA positive long extended and spindle-shaped stromal cells, and synthesis of type III collagen were observed in the subepithelial stromal layer corresponding to corneal haze in PRK and LASIK with denuded epithelium, but not in denuded epithelium alone and LASIK. CONCLUSION: The intact corneal epithelium may play an important part curbing subepithelial haze and differentiation of myofibroblasts in corneal wound healing.